Geographic access to mammography screening centre and participation of women in the Quebec Breast Cancer Screening Programme. Issue 10 (13th July 2013) - St-Jacques, Sylvie; Philibert, Mathieu D; Langlois, André; Daigle, Jean-Marc; Pelletier, Éric; Major, Diane; Brisson, Jacques
Abstract : Background: This study evaluated the impact of distance between women's residences and designated screening centres (DSC) on participation in the Quebec Breast Cancer Screening Programme, whether this impact varied according to the rural–urban classification and the proportion of participants who used the DSC nearest to their home. Methods: Travel distance between the residence of 833 856 women and the nearest DSC (n=85) was estimated. Data were obtained from administrative and screening programme databases. The analysis made use of a log-binomial regression model adjusting for age and material and social deprivation. The proportions of participants who used the DSC nearest to their residence were measured. Results: Compared to women living <2.5 km from a DSC, absolute decreases of 6.3% and 9.8% in participation rate were observed for distances of 50.0 to <75.0 km (rate ratios (RR)=0.88, 95% CI 0.86 to 0.89) and ≥75.0 km (RR=0.81, 95% CI 0.79 to 0.83), respectively. The lowest participation (42%) was observed in Montreal Island. The distance at which participation started to decrease materially varied according to rural–urban classification. Participation rates decreased at distances of ≥25.0 km in the Montreal suburbs and midsize cities, at ≥12.5 km in small cities and at ≥50.0 km in rural areas (interaction p<0.0001). The proportion of participants who had their mammography at the nearest DSC decreased with increasing distance. Conclusions: Distance affects participation and this effect varies according to rural–urban classification. The lower participation in Montreal Island, where all women lived <12.5 km from a DSC, argues for a major impact of other characteristics or other dimensions of accessibility.